E-Government in MSME Data Management: A Study of the APIK Website Pasuruan Regency Cooperatives Office - Muhammad Arif Rahman Al Syanov; Muhammad Caroin; Anni Iftitachul Faricha (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze the implementation of E-Government in managing Micro, Small, and Medium Enterprises (MSMEs) data through the APIK website (Application for Empowerment and Capacity Improvement of MSMEs) under the Cooperative Office of Pasuruan Regency. The study is based on the need for digitalization to enhance effective, transparent, and accountable MSME data governance. Using a qualitative descriptive method, data were collected through interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model. The results show that the e-Administration dimension improves efficiency and accelerates data validation, while e-Citizen and e-Services expand public access to digital services and encourage MSME participation in the data system. The e-Society dimension emerges through digital community involvement and collaboration among business actors facilitated by APIK. However, challenges such as data entry errors and limited socialization remain. The study concludes that APIK has strong potential as a strategi c innovation in strengthening digital MSME governance, recommending enhanced digital literacy, technical assistance, and inter-agency data integration to support an inclusive e-Government framework.